Case Study on Management of Overweight (Sthoulya) through Ayurveda - Ashvini D. Pardhekar; Shreya Satpute; Abhilash Pardhekar; Manisha Davkare (Journal of Pharmacy and Bioallied Sciences)
Modernization, affluence, and advancements in science and technology have led to increasingly sedentary lifestyles. This unintentionally invites a range of health issues, one of which is Sthoulya (overweight), which can affect physical, mental, and social health. Sthoulya refers to an individual who has excessive fat and flesh accumulation, causing a disproportional enlargement of the buttocks, belly, and breasts without a corresponding increase in energy. A 38-year-old female patient presented with weight gain, excessive hunger, sleep and sweating, lack of enthusiasm, and bad body odor. Before and after therapy, the patient was assessed for subjective and objective characteristics. There was an improvement in subjective parameters, anthropometric measurements, body mass index (BMI), and body weight after treatment. The combination therapy comprising Tryushanadi Guggul, Udvartan with Vacha Churna, and Peti Sweda demonstrated effectiveness in improving the lipid profile and anthropometric measurements of the patient over a 30-day treatment period.